2024
DOI: 10.1002/adfm.202309296
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive Emission from Hybrid Metal Halides

Kunjie Liu,
Ke Liu,
Shiqiang Hao
et al.

Abstract: Stimuli‐responsive photoluminescent (PL) materials have attracted considerable attention in recent years owing to their potential applications in anti‐counterfeiting, information encryption, and sensing. Further investigations of the transformation mechanism and potential applications of stimulus‐responsive PL materials are considerably important. In the current study, an organic–inorganic metal halide, C9H15N3SbCl5 ([C9H13N3]2+ is a 1‐(2‐pyridyl) piperazine cation) is obtained, which exhibits a 0D structure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Previously reported work has demonstrated that the PL emission intensity of 0D manganese halides is sensitive to the external chemical environment, especially for the polar solvents, which inspires us to explore the potential applications of title halides in detection and sensing performance toward chemical molecules. Herein, we select halide 1 as an example considering the high PLQY and emission color purity. To achieve a high-performance detection result, a thin halide@PVP composite-based film was prepared by depositing the microcrystal 1 on transparent glass, which displays the same green light emission under irradiation of 254 nm UV light (Figures S15 and S16). As shown in Figure a, when the film based on halide 1 was exposed to a moist atmosphere with a relative humidity of 60%, the luminescence of the film was weakened in different attenuation degrees along with the exposure time increasing.…”
Section: Resultsmentioning
confidence: 99%
“…Previously reported work has demonstrated that the PL emission intensity of 0D manganese halides is sensitive to the external chemical environment, especially for the polar solvents, which inspires us to explore the potential applications of title halides in detection and sensing performance toward chemical molecules. Herein, we select halide 1 as an example considering the high PLQY and emission color purity. To achieve a high-performance detection result, a thin halide@PVP composite-based film was prepared by depositing the microcrystal 1 on transparent glass, which displays the same green light emission under irradiation of 254 nm UV light (Figures S15 and S16). As shown in Figure a, when the film based on halide 1 was exposed to a moist atmosphere with a relative humidity of 60%, the luminescence of the film was weakened in different attenuation degrees along with the exposure time increasing.…”
Section: Resultsmentioning
confidence: 99%
“…The ABX 3 metal halide perovskite (A = organic cation, B = metal cation, and X = halogen anion) structure, composed of corner-shared MX 6 octahedral building blocks, has seen rapid development in recent years and is now a focus of optoelectronic research. The morphology and size of embedded organic cations can largely determine the molecular structure and dimension . Low-dimensional [one-dimensional (1D) and zero-dimensional (0D)] structures with higher quantum constraints often lead to a more localized electron distribution, resulting in intense photoluminescence properties. B-site metal ions are typically used as luminescent centers in organic–inorganic hybrid perovskites. , Furthermore, the selection of X (Cl, Br, or I) will affect the optical and electronic band structures of these hybrid perovskites. …”
Section: Introductionmentioning
confidence: 99%
“…That is, the external stimulation significantly changes the bond length and bond angle of the inorganic components, 29,30 the coordination number of metal ions, the coordination/insertion of the guest molecules, or the dimensional change of BX n m − . 31–42 For example, Xiao et al 43 reported that the bond length and bond angle of Sn 2+ -IOMHs C 4 N 2 H 14 SnBr 4 change significantly with increasing pressure, resulting in a larger dipole moment and higher structural and excited state distortion. Peng et al found that the hydrogen bond strength in [EtPPh 3 ] 2 [SbCl 5 ] can be influenced by diverse organic functional groups upon exposure to different organic gases.…”
Section: Introductionmentioning
confidence: 99%